The Influence of The Covid-19 Pandemic on Tax Avoidance - Wicaksono, Ivonne Caroline; Adi, Priyo Hari (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
The Covid-19 pandemic contributes to the slowdown of Indonesia's economy; therefore, the government provides tax incentives to particular sectors during this pandemic. This research seeks to investigate the influences of the Covid-19 pandemic and tax incentives on tax avoidance. This research uses Multiple Regression Analysis to process research data of firms from consumer financing institutions, insurance firms, and banks listed on the Indonesia Stock Exchange (IDX). We generate the data from IDX's and firms' official websites. This research documents that the Covid-19 pandemic has a significant relationship with tax avoidance, and firms receiving tax incentives during the Covid-19 pandemic are less likely to avoid taxes. In conclusion, during the Covid-19 pandemic, firms tend to avoid taxes to reduce losses and avoid bankruptcy. However, tax incentives given by the government demotivate firms to avoid taxes.